(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The study examined cassava products value addition in Nasarawa state, Nigeria. Data were collected from 1,360 respondents and analysed using general linear model statistics. The result showed that boiled cassava root, cassava bread, cassava chips, cassava flakes, garri, High Quality Cassava Flour (HQCF) and meat pie had mean incomes of N555.00, N3,429.17, N225.00, 642.86, N3,642.86, N119.00, 127.66, N121, 288.37 and N1,490.00, respectively. The mean incomes from cassava chips, HQCF, and garri were significantly (p<0.05) higher than mean incomes of the backed Cassava products (Cassava flakes, meat pie, Cassava bread and boiled Cassava roots). Also, the mean income differential of cassava flakes, garri, HQCF and meat pie were significant at P<0.05. Processors that produce only boiled cassava roots, cassava bread, chips, flakes, garri, HQCF and meat pie (level 1) had mean incomes of N555, N3, 429.17 N 196,666.67, N3, 642. 86. N 172,319.15 N 108, 683.72 and N 1, 490, respectively. Those of them that processed cassava roots into cassava chips and HQCF or garri (level 2) recorded mean income of N 147,102.33 and those that processed cassava roots into cassava chips, garri and HQCF (level 3) settled with mean income of N 222,441.86. Comparatively, mean income of level 1 is significantly (P<0.05) lower than the mean incomes of levels 2 and 3 (with differences of N 58018.89 and N 98,955.89). However, the mean income differential between levels 2 and 3 is not significantly different. Processors should concentrate on processing chips, garri and or HQCF for better economic gain.